Children, digital educational poverty and the pandemic. A starting point or a dead-end constraint? - De Stefani, Federica (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
The pandemic has helped accelerate the process of digitisation of the population, regardless of age. Adults have experienced various forms of working from home, improperly called smart working, often with inappropriate devices, while children and young people have been forced to pursue their education at home, through distance learning. In this way, thanks to digital technology, both work and education were able to continue on their path, although the pandemic forced users to use tools for which they had not acquired the necessary skills, now indispensable for both personal and professional use.